Bipolar type indolocarbazole host for green phosphorescent organic light-emitting diodes - Im, Yirang; Han, Si Hyun; Lee, Jun Yeob (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] A bipolar host designed using indolocarbazole as a bipolar moiety was developed by coupling two indolocarbazole moieties via a phenyl linker. The indolocarbazole derived hosts could carry holes and electrons in the emitting layer, functioning as bipolar hosts in the green phosphorescent organic light-emitting diodes. The linker based molecular design was superior to the directly coupled molecular design to match carrier balance for high quantum efficiency in the green phosphorescent devices.